KK2845, a PBD dimer-containing antibody-drug conjugate targeting TIM-3-expressing AML - Zou, Jian; Kinosada, Haruka; Takayanagi, Shin-ichiro; Ishii, Toshihiko; Amano, Toru; Nihira, Kaito; Kanie, Shohei; Adachi, Maiko; Tahara, Harunobu; Sakoda, Teppei; Kikushige, Yoshikane; Akashi, Koichi; et al. (Leukemia, 2025)
Acute myeloid leukemia (AML) is a common hematopoietic malignancy with high recurrence rates, and there is an urgent need for new therapeutic agents. T-cell immunoglobulin mucin-3 (TIM-3) is expressed on the surface of both LSCs and blasts in most AML patients, but not in normal hematopoietic stem cells (HSCs). We have developed KK2845, an antibody drug conjugate (ADC) that consists of an anti-TIM-3 fully human IgG1 antibody, a valine-alanine linker and a highly potent DNA cross-linking pyrrolobenzodiazepine (PBD) dimer SG3199. KK2845 exhibited potent cytotoxicity against AML cells both in vitro and in vivo. The cytotoxicity against AML cells was almost comparable between KK2845 and CD33-ADC, an anti-CD33 antibody conjugated with PBD dimer that has shown high remission rates in clinical studies. In addition to the cytotoxicity depending on PBD dimer, KK2845 also showed potent antibody-dependent cell cytotoxicity (ADCC) activity against AML cells. KK2845 showed less cytotoxicity against human normal bone marrow cells than CD33-ADC. The pharmacokinetics of KK2845 in cynomolgus monkey after intravenous infusion demonstrated a favorable profile. Taken together, these data suggest that KK2845 could be a novel ADC therapeutic in AML.